(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A propelled vehicle checking and following framework considering Embedded Board and android application is outlined and actualized for observing the school vehicle from any area A to area B at constant. The proposed framework would make great utilization of innovation that consideringArduino Unoand smartphone android application. The proposed framework utilizes the internet of things (IoT) and GPS, where IoT sends an information to any guardian or owner regarding the vehicle status and GPS sends the current area of the vehicle.